2020
DOI: 10.1097/bpo.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

Pulling the Trigger: Recommendations for Surgical Care of the Pediatric Trigger Thumb

Abstract: Background: Despite being a common pediatric hand condition, there are few clear guidelines regarding the optimal management of pediatric trigger thumb. Our primary aim was to help guide surgical management of this disorder by establishing a treatment algorithm on the basis of our institution’s experience. Methods: This is an institutional review board-approved retrospective study of all patients with idiopathic trigger thumbs from 2005 to 2015 at a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 9 publications
2
27
0
1
Order By: Relevance
“…This is a higher rate of surgery with a shorter period of observation than that recommended by the recent literature, which supports initial nonoperative treatment for up to 5 years with up to 76% of spontaneous resolution. 5,6,15 Dittmer et al 22 reported a single-institution experience of treating 193 trigger thumbs and found that 33% of pediatric patients underwent surgery at the average age of 3 years, without any observational period, demonstrating the common practice of early trigger thumb surgery in the United States. This pattern of practice mirrors our study showing that most (72%) of the patients who undergo surgery do so at the age between 2 and 5 years without an adequate observational period.…”
Section: Discussionmentioning
confidence: 99%
“…This is a higher rate of surgery with a shorter period of observation than that recommended by the recent literature, which supports initial nonoperative treatment for up to 5 years with up to 76% of spontaneous resolution. 5,6,15 Dittmer et al 22 reported a single-institution experience of treating 193 trigger thumbs and found that 33% of pediatric patients underwent surgery at the average age of 3 years, without any observational period, demonstrating the common practice of early trigger thumb surgery in the United States. This pattern of practice mirrors our study showing that most (72%) of the patients who undergo surgery do so at the age between 2 and 5 years without an adequate observational period.…”
Section: Discussionmentioning
confidence: 99%
“…TT treatment is simple but remains controversial. [18][19][20] The metachronism of bilateral TT may lead to additional surgery under anesthesia, which poses a dilemma for the surgeon. Knowledge of the temporal development of bilateral TT may be useful for preventing a second surgery and providing evidence for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, bilateral thumb involvement increases the risk of surgery. Dittmer et al 18 suggested that according to the Sugimoto classification, stage IV thumbs should undergo surgery without an observation period, whereas stage II and stage III thumbs could be safely observed for at least 1 year before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…sogar Operationen verhindern, v. a. bei dem falschen Verdacht einer Sehnenruptur als Differenzialdiagnose. In vielen Fällen kann durch das Erkennen der Pathologie sowie adäquate konservative Therapie durch einen geschulten Handtherapeuten mit Einbinden der Eltern hier eine OP vermieden werden 7 .…”
Section: Diagnostikunclassified